1999
DOI: 10.1111/j.1528-1157.1999.tb00706.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prognosis for Control of Seizures with Medications in Patients with MRI Evidence for Mesial Temporal Sclerosis

Abstract: Not all patients with MTS are medically intractable; 25% of the patients in our study achieved complete control while receiving medication. Poor seizure control was related to an early age of seizure onset, a history of febrile convulsions, and epileptiform discharges on the EEG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
4
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 21 publications
9
62
4
4
Order By: Relevance
“…10,13,15,[19][20][21][30][31][32][33][34] In general our findings agree with the results of previously published studies. Similar to our findings previous studies have also reported that patients with partial epilepsy have a greater chance to develop drug-resistant epilepsy than patients with generalized epilepsy.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…10,13,15,[19][20][21][30][31][32][33][34] In general our findings agree with the results of previously published studies. Similar to our findings previous studies have also reported that patients with partial epilepsy have a greater chance to develop drug-resistant epilepsy than patients with generalized epilepsy.…”
Section: Resultssupporting
confidence: 93%
“…19 A yet unresolved debate is whether the number of past seizures or the etiology of epilepsy and especially hippocampal atrophy carry a prognostic value. 13,19,21,[30][31][32][33] With respect to the etiology of epilepsy we found no significant difference between patients with cryptogenic (remote symptomatic) and symptomatic epilepsy. 32 However, we did not examine specific causes of symptomatic epilepsy, as the small number of patients with each specific etiology (for example our cohort included 29 cases with hippocampal atrophy and 25 cases with cortical dysplasia) precluded us from controlling for the past AED treatment history for each specific etiology.…”
Section: Resultsmentioning
confidence: 52%
“…The quantity of interictal spikes is predictive of severity in temporal lobe epilepsy [19]. Oligospikers, patients with temporal lobe epilepsy with less than 1 spike per hour, correlate with less severe epilepsy [20].…”
Section: Predictive Factors Of Refractorinessmentioning
confidence: 99%
“…In particular, hippocampal sclerosis and cortical dysgenesis were important indicators of a poor prognosis, whereas seizures in patients who had strokes, vascular malformations, or tumors were more likely to be controlled. However, other studies have found a better outcome for patients with medial temporal lobe epilepsy (MTLE), indicating an heterogeneous clinical presentation for patients with MR-detected mesial temporal sclerosis (14,15). Thus none of these markers is especially sensitive or specific for refractory epilepsy.…”
mentioning
confidence: 99%